A Glance on the Assessment of the Use of Information Resources Using Altmetrics - Firoozeh Dokhani; Amir Reza Asnafi (سیاست نامه علم و فناوری, 2020)
The present study intends to discuss the use of Altmetrics in evaluating the number of information resources used by libraries by a text-based approach. The present study is a systematic literature review using studying and analyzing and investigating texts. The use of Altmetrics in the library leads to an appropriate benchmark for the use of digital content and access to core and specific resources. This helps libraries to receive grants and scholarships from international organizations for their research projects. Altmetrics inform researchers about the impact of their scientific resources on the inside and outside the organization and make individuals aware of the impact of scientific resources around them. In this situation, not only are librarians aware of the scientific activities of various university groups, but they also can bring students with them. Library management can provide the affiliated organization or university with a complete report of the outstanding scientific activities of its researchers in cyberspace.